PATHOPHYSIOLOGY OF OBESITY- AN INSIGHT INTO THE MOLECULAR MECHANISM - DR. AMBILI REMESH (International Journal of Pharma and Bio Sciences, 2013)
Obesity is a multi factorial disease which involves complex molecular pathways is basically due to imbalance between energy intake and energy expenditure.Presumably other than genetic endowments, a series of biological events tip the fine balance of homeostatic mechanism of energy control and any shift in these regulatory pathways can result in obesity. Though the effect is not always predictable, once the homeostasis is altered it is very difficult to restore the balance. The primary regulating centre of energy intake is brain; the hypothalamus being the main integrating centre. The regulation of energy expenditure is still not clear. With very few pharmaceutical agents to curb this emerging public health problem, a better understanding of molecular mechanism of energy imbalance is well appreciated. This article gives an overview of molecular mechanism of patho physiology of obesity.